Ramie: A fibre crop of new opportunities - Saha, Dipankar; Sharma, A K; Laha, S K; Sinha, M K; Mahapatra, B S (Indian Farming, 2015)
It is difficult to obtain accurate information on the level of current imports of ramie fibre and fabric into India and the value of those imports. Ramie fibre is acknowledged as a high quality fibre but its production is labour intensive. The need for chemical treatment to extract the fibre has also been seen as a serious disadvantage. However, experience with many other crops shown that all facets of production and processing can now be mechanised and this could make Indian-grown fibre competitive with production from traditional growing areas.